2009
DOI: 10.1103/physreve.79.056702
|View full text |Cite
|
Sign up to set email alerts
|

Computation of the response functions of spiral waves in active media

Abstract: Rotating spiral waves are a form of self-organization observed in spatially extended systems of physical, chemical, and biological natures. A small perturbation causes gradual change in spatial location of spiral's rotation center and frequency, i.e., drift. The response functions ͑RFs͒ of a spiral wave are the eigenfunctions of the adjoint linearized operator corresponding to the critical eigenvalues =0, Ϯ i. The RFs describe the spiral's sensitivity to small perturbations in the way that a spiral is insensit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
91
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(91 citation statements)
references
References 41 publications
0
91
0
Order By: Relevance
“…Importantly, it was found that response functions (RFs) are closely related to the symmetries of the RDE (2) in two spatial dimensions [7,27], which allows one to compute them numerically for given diffusion matrix P and reaction kinetics F(u) [30,61]. Before studying the RDE in a rotating frame of reference, it is necessary to reconcile sign conventions for the angular frequency, since we will be using an extension of the DXSPIRAL program of Biktasheva et al [61] to compute RFs.…”
Section: Response Functionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Importantly, it was found that response functions (RFs) are closely related to the symmetries of the RDE (2) in two spatial dimensions [7,27], which allows one to compute them numerically for given diffusion matrix P and reaction kinetics F(u) [30,61]. Before studying the RDE in a rotating frame of reference, it is necessary to reconcile sign conventions for the angular frequency, since we will be using an extension of the DXSPIRAL program of Biktasheva et al [61] to compute RFs.…”
Section: Response Functionsmentioning
confidence: 99%
“…In this section, we briefly review response function theory and introduce sign conventions for going from the Cartesian basis of [7,22,25] to the complex-valued representation of [8,61].…”
Section: Response Functionsmentioning
confidence: 99%
See 3 more Smart Citations